A bi-objective model for the location of relief centers and distribution of commodities in disaster response operations - Moreno, Alfredo; Ferreira, Deisemara; Alem, Douglas (Dyna (Medellín, Colombia), 2017)
Abstract Consequences of natural disasters in recent years have shown the complexity of these situations. In disaster situations, the location of relief centers, the distribution of supplies and the fleet sizing are some of the most important decisions. In most cases the execution of this operations lead to contradictory objectives, mainly, logistic costs and unmet demand costs. On the one hand, minimize unmet demand implies higher logistics costs. On the other hand, minimize logistics costs without considering the unmet demand may lead with an inefficient attendance in the affected areas. In this paper, we propose a bi-objective stochastic programing model for the integrated problem of location-distribution and fleet sizing. We solve instances based on the mega disaster in the Mountain Region of Rio de Janeiro in 2011. We compare the solutions of a bi-objective model in respect to solutions of a mono-objective version, highlighting the advantages and disadvantages of each model.